Sequential Extraction of Bioactive Saponins from Cucumaria frondosa Viscera: Supercritical CO2–Ethanol Synergy for Enhanced Yields and Antioxidant Performance - Jianan Lin; Guangling Jiao; Azadeh Kermanshahi-pour (Marine Drugs)
This study investigates the sequential extraction of lipids and saponins from C. frondosa viscera. Lipids were extracted using supercritical carbon dioxide (scCO2) in the presence of ethanol (EtOH) as a co-solvent. Subsequently, the lipid-extracted viscera underwent three saponin extraction approaches, scCO2-scCO2, scCO2-EtOH, and scCO2-hot water, resulting in saponin-rich extracts. Process parameter investigation for saponin extraction from scCO2-defatted viscera revealed minimal effects of temperature, pressure, extraction time, static extraction, and EtOH concentration on saponin yields, allowing for milder operational conditions (35 °C, 20 MPa, 30 min dynamic extraction, 75% EtOH at 0.5 mL/min) to achieve energy-efficient recovery. Continuous EtOH feeding predominates the scCO2 extraction of saponins. The sequential scCO2 extraction of lipid and saponins yielded saponins at 9.13 mg OAE/g, while scCO2 extraction of lipid followed by a 24 h 70% EtOH extraction of saponins achieved 16.26 mg OAE/g, closely matching the optimized ultrasonic-assisted extraction of saponins (17.31 mg OAE/g) from hexane-defatted samples. Antioxidant activities of saponin-rich extracts obtained in the sequential scCO2-EtOH extraction (17.12 ± 4.20% DPPH scavenging) and the sequential scCO2-scCO2 extraction (16.14 ± 1.98%) were comparable to BHT (20.39 ± 0.68%), surpassing that of hexane-defatted ultrasonic extracts (8.11 ± 1.16%). The optimized scCO2-EtOH method offers a sustainable alternative, eliminating toxic solvents while maintaining high saponin yields and bioactivity.